2020
DOI: 10.1016/j.coelec.2020.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Electrocatalytic reduction of CO2 in neat and water-containing imidazolium-based ionic liquids

Abstract: Energetically efficient electrochemical reduction of CO2 would offer the possibility of storing electricity from renewables in the form of fuels and other valuable chemicals. It may also help mitigate the increase of atmospheric CO2 associated with global warming. However, the process suffers from a low energy efficiency due to the large overpotentials required. In aqueous electrolytes, the competing hydrogen evolution reaction also decreases the faradaic efficiency (which contributes to the low energy efficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 46 publications
0
28
0
Order By: Relevance
“…[429] This approach speeds up the calculation and can be applied to larger and complex systems including electrolyte. [430][431][432][433] Machine learning is emerging as a promising computational tool for screening efficient catalysts based on experimental results and DFT calculations. Modeling catalyst surface chemistry is a multistep Figure 12.…”
Section: Carbon Dioxide Reduction Reactionmentioning
confidence: 99%
See 1 more Smart Citation
“…[429] This approach speeds up the calculation and can be applied to larger and complex systems including electrolyte. [430][431][432][433] Machine learning is emerging as a promising computational tool for screening efficient catalysts based on experimental results and DFT calculations. Modeling catalyst surface chemistry is a multistep Figure 12.…”
Section: Carbon Dioxide Reduction Reactionmentioning
confidence: 99%
“…[ 429 ] This approach speeds up the calculation and can be applied to larger and complex systems including electrolyte. [ 430‐433 ]…”
Section: Perspectives and Outlookmentioning
confidence: 99%
“…However, CO 2 conversion without a catalyst is not possible due to the high thermodynamic stability of CO 2 (Δ G f ° = −400 kJ mol –1 ) . Electrocatalysis of CO 2 is a promising approach, e.g., for the production of ethanol or formic acid as fuel carriers and has recently gained considerable attention. , However, in aqueous electrolytes, substantial overpotentials for reduction of CO 2 exists and CO 2 reduction can compete with hydrogen evolution reactions and thus impair CO 2 electrocatalysis. The origin of existing overpotentials lies partly in the formation of a CO 2 radical anion as a necessary reaction intermediate …”
Section: Introductionmentioning
confidence: 99%
“…The mechanism of the reduction of CO 2 to HCOOH is still controversial after more than 40 years of study. [4][5][6][7][8][9][10][11][12][13][14][15] Hori and co-workers [1,2] suggested that CO 2adsorbs on the electrode surface through its carbon atom, and that whether CO or HCOOH is the final product of the 2-electron reduction depends on the corresponding adsorption energy. Figure 1 is an illustration of these two reaction pathways.…”
Section: Introductionmentioning
confidence: 99%